2021
DOI: 10.3390/healthcare9060743
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Open Medical School without Checkerboards during the COVID-19 Pandemic: How to Flexibly Self-Manage General Surgery Practices in Hospitals?

Abstract: Background: Can we create a technological solution to flexibly self-manage undergraduate General Surgery practices within hospitals? Before the pandemic, the management of clerkships was starting to depend less on checkerboards. This study aims to explore undergraduates’ perceptions of doing rotations in teaching hospitals using different teaching styles and elicit their views regarding the options of managing practices to design a mobile app that substitutes for checkerboards. Methods: In this sequential expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Online tests including a broad interface of questions and automatic verification of answers are now available, as well as self-study tests with explanations and decision-making labyrinths which encourage creative thinking [ 20 , 21 , 22 ]. The authors of papers [ 23 , 24 , 25 , 26 ] have published very interesting recent examples of the usage of technological innovation in medicine. In paper [ 23 ] by Guiter et al, the authors present the development of remote online collaborative medical school pathology and explain how students across several international sites, throughout the COVID-19 pandemic, could control the digital slides and offer their own diagnoses, followed by group discussions.…”
Section: Technologies In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Online tests including a broad interface of questions and automatic verification of answers are now available, as well as self-study tests with explanations and decision-making labyrinths which encourage creative thinking [ 20 , 21 , 22 ]. The authors of papers [ 23 , 24 , 25 , 26 ] have published very interesting recent examples of the usage of technological innovation in medicine. In paper [ 23 ] by Guiter et al, the authors present the development of remote online collaborative medical school pathology and explain how students across several international sites, throughout the COVID-19 pandemic, could control the digital slides and offer their own diagnoses, followed by group discussions.…”
Section: Technologies In Educationmentioning
confidence: 99%
“…In paper [ 23 ] by Guiter et al, the authors present the development of remote online collaborative medical school pathology and explain how students across several international sites, throughout the COVID-19 pandemic, could control the digital slides and offer their own diagnoses, followed by group discussions. In publication [ 24 ] by Guadalajara et al, the authors demonstrate whether it is possible to create a technological solution to flexibly self-manage undergraduate general surgery practices within hospitals. In this interesting research study, it was proven that the usage of innovative educational technology could be efficient.…”
Section: Technologies In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also seen advances in e-learning approaches among a number of countries, including higher-income countries, to devise different teaching approaches. These include mobile applications for practical sessions, addressing concerns with e-exams, and universities combining to offer virtual microscopy and Zoom videoconferencing to teach pathology [ 84 , 85 , 86 , 87 ]. The situation in these countries, as well as Saudi Arabia ( Box 1 ), can be different to experiences in Jordan and other LMICs with appreciably fewer resources to instigate e-learning and other approaches [ 50 , 88 , 89 , 90 ], as well as across Africa ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has led to both a higher prevalence of mental health and substance use symptoms and disorders globally, and recurrences or worsening of symptoms among people with mental disorders [ 22 ]. Studies involving patients have shown higher levels of depression, anxiety, and sleep disturbances in these individuals during strict lockdown measures in many countries that have flexibly managed hospital practices during pandemic times [ 23 , 24 , 25 , 26 ], including Spain [ 27 , 28 ]. Therefore, in this “post-COVID-19 era”, it is necessary to properly assess and address the extent of this mental health collateral damage and the usage of mobile health (mHealth) tools to cover the reported mental health services gap.…”
Section: Introductionmentioning
confidence: 99%